Compliance and Usability of Weber and Rinne’s Tests For Audio Acuity Among Primary School Children From a Health Resource Poor Community - Ahmadu, Baba Usman; Solomon, Joshua Danji; Zira, Fate Bala; Aisha, Abdallah Joda; Rimamchika, Musa; Ibrahim, Ahmad (Journal of Nepal Paediatric Society, 2013)
Background: Normal auditory acuity is needed for transmission and reception of speech between teachers and students, and from student to student for effective communication and learning. Hearing impairment in school children will potentially cause difficulty perceiving speech clearly in the educational environment. Materials and Methods: Auditory acuity measurements were conducted on 300 primary school children using the Weber and Rinne’s tests. Results: Nearly all the children 292 (97.3%) had good hearing. Eight (2.7%) had ipsilateral conduction hearing impairment. Of these, 5 (62.5%) occurred on the right and 3 (37.5%) on the left ear; they were referred to the otorynolaryngologist for further evaluation and management. Conclusion: Our subjects demonstrated high compliance to Weber and Rinne’s tests which were found to be usable in screening hearing impairment in school children. These tests can be incorporated into the school health programmes in resource poor countries where high tech hearing screening facilities are not readily affordable and available. In addition, the test can be conducted at primary health centers thereby decongesting both secondary and tertiary health facilities. DOI: http://dx.doi.org/10.3126/jnps.v33i2.7673 J Nepal Paediatr Soc. 2013; 33(2):95-98